Pengaruh Siaran Langsung dan Ulasan Pelanggan Online serta Citra Merek Terhadap Keputusan Pembelian Online - Cicilia Chika Artamevia; Dwi Martianti (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The purchasing decision is an essential part of consumer behavior that describes how individuals or groups make choices, use, and evaluate a product to meet their needs and desires. The decision-making process is heavily influenced by the information available regarding the product's quality, the brand's credibility level, and the benefits or usefulness of the product for consumers. This research aims to analyze the extent to which live broadcasts, online customer reviews, and brand image can influence purchasing decisions, as well as to understand  the interaction among these three factors in the context of marketplace platforms (e commerce), particularly Tokopedia. The data used is derived from primary sources using a survey method as a data collection approach,conducted through the distribution of questionnaires and analyzed using multiple linear regression methods. The  population used as a reference is Generation Z who use the Tokopedia application and reside in the Samarinda area. The results of the study indicate that the live broadcast feature on the Tokopedia platform is effective in building consumers' confidence to purchase products, through real-time explanations, interaction with hosts, and limited-time offers. The research results also confirm that reviews from other users, especially those with logical arguments and a significant number of reviews, play a dominant role in influencing the purchasing decisions of Generation Z consumers who tend to rely on social proof. Furthermore, consumers are more likely to purchase products from brands with a strong visual identity, clear differentiation, and consistency in communication through digital platforms